Pojęcie rodziny a jej ochrona w procesie stanowienia i stosowania prawa - Stojanowska, Wanda; Kosek, Mirosław (Ius Matrimoniale, 2017)
The subject of this article is to discuss the notion of family within the procedure of enacting and applying the law. The authors analyze the way of defining the said notion by the legislator in a selection of legislative acts situated in the context of the provisions of the Polish constitution as well as the Family and Guardianship Code pertaining to the notion of family. Additionally, the authors take into consideration the Polish judicial practice related to the court interpretation of the said notion. The article contains several suggestions and proposals de lege lata and de lege ferenda. The authors propose, among other things, an amendment to the procedure of law enactment by agreeing upon a single definition of family within the entire legal system, which has already been introduced in the Family and Guardianship Code, so that the definition would not need to be modified depending on the subject of the provision of law, and so that the legislator would be allowed to distribute the rights related to the family also to other entities without having to incorporate the aforementioned entities in an “unnatural” way into the notion of family.